Peran Komunikasi dalam Meningkatkan Kinerja Pegawai RSD Dr. Soebandi - Khotimah, Khusnul; Ilyasi, Ach (Majalah Ilmiah DIAN ILMU, 2023)
RSD dr. Soebandi is the main referral hospital appointed by thegovernment, so it is required to provide excellent service, supported by 1,110employees, consisting of doctors, nurses, administrative staff, and other staffsuch as midwifery staff, nutrition staff, pharmacy and environmental healthstaff. However, the results of initial observations are based on existing data at RSD dr. Soebandi showed that the performance of hospital services still doesnot meet the targets set by the RSD dr. Soebandi himself and nationalrealization standards. This study used qualitative research methods. Datacollection techniques were carried out by means of observation, in-depthinterviews and documentation. Test the validity of the data using the sourcetriangulation method. This research uses interactive model data analysistechniques. Based on the results of interviews and observations conducted withRSD dr. Soebandi employees stated that the existing communication was goodbut the intensity of communication between employees needed to be increased,by holding regular formal meetings in the form of, for example, weeklymeetings and inter-unit meetings.